Tween 20‐Assisted Synthesis of Uniform Mesoporous Silica Nanospheres with Wormhole Porosity for Efficient Intracellular Curcumin Delivery. Issue 11 (23rd March 2018) - Maqbool, Qysar; Chanchal, Abhishek; Srivastava, Aasheesh
Abstract: We report a green and straightforward protocol to prepare uniform mesoporous silica nanospheres (MSNs) as well as core/shell‐like spherical particles by utilizing small amounts of Tween 20, a biocompatible and biodegradable surfactant. Due to small amount of surfactant employed in the synthesis, these MSNs can be easily purified and readily dispersed in water. TEM analysis showed presence of wormhole‐like framework‐confined mesoporosity along with high surface area (upto 250 m 2 /g) in these MSNs. Size‐tunability of these nanospheres was achieved by simple variation of the ethanol:water ratio during the synthesis. Powder X‐ray diffraction (XRD) and low angle XRD, respectively, showed amorphous nature and similar pore ordering for all the samples prepared using this protocol. These MSNs showed effective, post‐synthetic uptake of model hydrophobic drug curcumin to yield stable aqueous dispersions. High biocompatibility and ready internalization by mammalian cells mainly through clathrin‐independent, caveolae‐ and lipid raft‐mediated endocytosis was observed for these MSNs. Efficient intracellular delivery of curcumin using these MSNs was achieved in MDA‐MB‐231 (Breast cancer) cells. Thus, this work offers facile protocol for synthesis of uniform and biocompatible MSNs with promising drug delivery capabilities. Abstract : Biocompatible surfactant Tween 20 yields uniform mesoporous silica nanospheres with wormhole porosity through modified Stöber method.